Management strategies to optimize peanut yields in Argentina under restrictive environmental conditions - Ricardo Javier Haro; Gustavo Ovando (Farming System)
Peanut production in Argentina is predominantly rainfed, with considerable variability in rainfall patterns within and between seasons. This variability results in droughts of varying duration and severity, which can significantly reduce yields. Water availability is, therefore, a critical factor in determining the optimal sowing date. The objectives of this study were to (i) assess the effects of sowing dates and water gradients on peanut yield and crop traits at two representative sites in the central peanut-producing region, and (ii) identify management strategies that optimize yield under water-limited conditions. Seasonal and annual analyses were conducted, incorporating water availability at sowing, environmental conditions, site characteristics, management practices, and cultivars. The Cropping System Model CROPGRO-Peanut was employed to simulate the impacts of those factors. Seasonal analysis revealed that delayed sowing dates consistently led to yield reductions, irrespective of water availability, with decreases in seed number, maximum leaf area index, total biomass, and water use efficiency. These yield reductions were more pronounced under lower water availability at sowing. When sown late, annual analysis indicated that combining an early cultivar and progressively narrowing row spacing resulted in increased yields. In contrast, intermediate-cycle and late cultivars experienced yield declines due to lower radiation and temperature levels. Differences in yield were also explained by the varying contributions of transpiration and evaporation to total water use. Our findings underscore the importance of management decisions in influencing water use components, with soil water-holding capacity playing a key role in crop performance. This study provides valuable insights for developing adapted management practices to improve productivity in temperate regions under water-limited conditions.